Challenges and successes in the propagation of the Shoebill Balaeniceps rex: with detailed observations from Tampa's Lowry Park Zoo, Florida. Issue 1 (24th October 2013) - Tomita, J. A.; Killmar, L. E.; Ball, R.; Rottman, L. A.; Kowitz, M.
<x xml:space="preserve">Abstract</x> The Shoebill Balaeniceps rex is categorized as Vulnerable on the International Union for Conservation of Nature Red List and past estimates of the wild population range from 5000 to fewer than 10 000 birds. The Shoebill Single Species Action Plan is currently in review and may better define the number of Shoebills remaining in the wild. The Shoebill population in captivity consists of only 40 [21.18.1 (♂.♀.?)] birds at 16 wildlife institutions worldwide. Successful propagation of species with high conservation value is dependent upon understanding the natural history and conservation needs of the taxon, providing appropriate husbandry, and optimizing health and nutrition. To date, only three Shoebill chicks are known to have been hatched in captivity. The first two hatched in July 2008 at Pairi Daiza (formerly Parc Paradisio) in Belgium. These chicks were hand reared and are still surviving at the time of writing. On 26 December 2009, Tampa's Lowry Park Zoo, FL, USA, became the first wildlife institution in North America to hatch a Shoebill chick and just the second institution worldwide. This chick was parent reared with careful monitoring by staff. The chronologies of this hatching as well as other significant experiences are detailed in this article.